EVALUATION OF LOCAL ANAESTHETIC AND ANTIPYRETIC ACTIVITY OF TERMINALIA CHEBULA RETZ IN EXPERIMENTAL ANIMAL MODELS - RAJYALAKSHMI.N,; NAGESH RAJU.G,; RAMANATH.B, (International Journal of Pharma and Bio Sciences, 2015)
Dry fruit of Terminalia chebula is used in leprosy, anemia, narcosis, piles, chronic, heart disease, diarrhea, anorexia, cough and excessive secretion of mucus. The present study was undertaken to evaluate the local anesthetic and antipyretic activity of T.chebula in experimental animal models. Ethanolic extract of T.chebula (EETC) was tested in local anesthetic action by (i) intracutaneous wheal in guinea pigs and (ii) plexus anesthesia in frogs. In both the models, 2% xylocaine was used as the standard drug. Brewer’s east induced pyrexia in rats before and after treatment of EETC compared with paracetamol. The test drug in concentrations of 10% and 20% produced 70.56% and 87.56 % anesthesia respectively by the intracutaneous wheal compared to 97.64% anesthetic effect produced by 2% xylocaine (P<0.001). The mean onset of anesthesia with the test drug was 5.33±0.47 min compared to 2.75±0.35 min (P<0.001) for the standard drug in the plexus anesthesia model. In the anti-pyretic model, EETC in doses of 400 and 600 mg produced dose-dependent reduction in mean temperature at various hours of observation. The present study shows that EETC has significant local anesthetic and antipyretic activities.